2022
DOI: 10.1111/codi.16136
|View full text |Cite
|
Sign up to set email alerts
|

Robotic beyond total mesorectal excision surgery for primary and recurrent pelvic malignancy: Feasibility and short‐term outcomes

Abstract: Aim: To explore the feasibility and safety of robotic beyond total mesorectal excision (TME) surgery for primary and recurrent pelvic malignancy.Methods: Patients undergoing robotic beyond TME resections for primary or recurrent pelvic malignancy between July 2015 and July 2021 in a public quaternary and a private tertiary centre were included. Demographic and clinical data were recorded and outcomes analysed.Results: Twenty-four patients (50% males) were included, with a median age of 58 (45-70.8) years, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Recent literature has shown that robotic-assisted bTME procedures have acceptable shortterm safety (Clavien-Dindo > IIIa complication rate of 22.1%; R1 rate of 4.2%), early recovery and survival rates when performed at specialized centres. 22,23 The univariate analysis performed on the data in the current study demonstrated that minimally invasive procedures showed comparable or better DFS than reported for these previous studies (Table 4). However, this could be attributed to selection bias in view of the nature of procedures adopted in open surgery.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Recent literature has shown that robotic-assisted bTME procedures have acceptable shortterm safety (Clavien-Dindo > IIIa complication rate of 22.1%; R1 rate of 4.2%), early recovery and survival rates when performed at specialized centres. 22,23 The univariate analysis performed on the data in the current study demonstrated that minimally invasive procedures showed comparable or better DFS than reported for these previous studies (Table 4). However, this could be attributed to selection bias in view of the nature of procedures adopted in open surgery.…”
Section: Discussionsupporting
confidence: 67%
“…Although minimally invasive procedures were adopted in 51.3% of patients in the present study, some 87% were performed after 2018, with 7.5% of patients undergoing robotic surgery. Recent literature has shown that robotic‐assisted bTME procedures have acceptable short‐term safety (Clavien–Dindo > IIIa complication rate of 22.1%; R1 rate of 4.2%), early recovery and survival rates when performed at specialized centres 22, 23 4).…”
Section: Discussionmentioning
confidence: 99%
“…24 The median LOS of 6 days seems to be within the range of previously reported studies, with mean 5 days found after robotic TME surgery, 25 while 12 to 16 days are reported in small series on complex robotic bTME surgery. 26,27 The LOS in a previously published cohort operated with open bTME surgery at our institution, was median 10 or 15 days depending on deep SSI or not. 28 Although the cohorts are not case-matched, one could speculate that robotic surgery reduce LOS for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that robotic radical resection of rectal cancer is safe and feasible, with good medium and long-term effects [ 8 , 9 ]. The results of this study showed that the average operation time of robotic rectal cancer radical surgery was 183.6 ± 44.8 min, the amount of intraoperative bleeding was 54.8 ± 34.4 ml, and the number of cleaned lymph nodes during surgery was 15.3 ± 7.8, which were consistent with the trend matching research results [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%